Business Model Innovation and exaptation: A new way of innovating in SMEs. (January 2023) - Codini, Anna Paola; Abbate, Tindara; Messeni Petruzzelli, Antonio
Abstract: Although research underlines the need for SMEs to innovate their Business Model, they face considerable challenges in exploring external business opportunities and experimenting/developing their available resources in unexpected ways. We posit that one way that SMEs can innovate their Business Model is through exaptation, a discontinuous evolutionary process that allows utilizing and adapting existing resources in new application domains. Using a case study approach, we investigate the case of a SME that has successfully innovated its Business Model through exaptation. We then discuss how three key exaptation processes lead to value creation, delivery and capturing, thus supporting Business Model Innovation in SMEs. Highlights: Connecting the concept of Exaptation with Business Model Innovation. Providing guidelines for SMEs to fruitfully use Exaptation for Business Model Innovation. Identifying how key Exaptation processes activate Value Creation, Value Delivery and Value Capturing mechanisms.